2024
DOI: 10.1021/jacs.3c14409
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Cross-[4 + 2]-Cycloaddition/Decarboxylation of 2-Pyrones by Cooperative Catalysis of the Pd(0)/NHC Complex and Chiral Phosphoric Acid

Meng-Meng Xu,
Pei-Pei Xie,
Jun-Xiong He
et al.

Abstract: Here, we describe a cooperative Pd(0)/chiral phosphoric acid catalytic system that allows us to realize the first chemo-, regio-, and enantioselective sequential cross-[4 + 2]-cycloaddition/ decarboxylation reaction between 2-pyrones and unactivated acyclic 1,3-dienes. The key to the success of this transformation is the utilization of an achiral N-heterocyclic carbene (NHC) as the ligand and a newly developed chiral phosphoric acid as the cocatalyst. Experimental investigations and computational studies suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Several control experiments were conducted to gain some insights into the reaction pathway. First, the non-linear effect experiments indicated that the active catalytic species in the key cycloaddition step might be formed by coordination of two ligands with palladium(0), 15 and the apparently beneficial influence of phosphoric acid A2 on the enantioselectivity was noted (Scheme 4a), 13 which was further verified by using the corresponding sodium salt of A2 (Scheme 4b). Based on the above experiments and previous reports, 5,11 a plausible catalytic mechanism was proposed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several control experiments were conducted to gain some insights into the reaction pathway. First, the non-linear effect experiments indicated that the active catalytic species in the key cycloaddition step might be formed by coordination of two ligands with palladium(0), 15 and the apparently beneficial influence of phosphoric acid A2 on the enantioselectivity was noted (Scheme 4a), 13 which was further verified by using the corresponding sodium salt of A2 (Scheme 4b). Based on the above experiments and previous reports, 5,11 a plausible catalytic mechanism was proposed.…”
Section: Resultsmentioning
confidence: 96%
“…Further evaluation of analogous ligands revealed that L4 could significantly improve the diastereoselectivity (entries 7–10). A quick survey of additives showed that carboxylic acid had little impact on the results (entries 11 and 12), but racemic BINOL-based phosphoric acid A1 improved the enantioselectivity dramatically, 13 although giving a slightly reduced yield (entry 13). Delightfully, the use of R -BINOL-derived phosphoric acid A2 with sterically hindered 3,3′-substituents dramatically enhanced the reactivity, and excellent diastereo- and enantiocontrol were retained (entry 14), demonstrating that A2 might function as a Brønsted acid to increase the reactivity of the 1-azadiene intermediate.…”
Section: Resultsmentioning
confidence: 99%